(untitled) (Fiep Bulletin - online, 2014)
The literature points to studies on the behavior of the body in the consumption of oxygen at altitude and that individual can benefit from that difference in relation to its performance. This study aimed to assess and compare general will indirectly maximum oxygen uptake alveolar (VO max.) and maximum oxygen uptake by the myocardium (MVO max.) An athlete born in the 2 2 mode mountain bike acclimatization wills altitude of 838m above the sea that participated in the Pan American Games 2007 in Rio de CurvaeVO2máx (Test at 838m up sea level) 12,2 17,4 26,1 34,8 43,5 52,2 64,4 0,0 10,0 20,0 30,0 40,0 50,0 60,0 70,0 1 2 3 4 5 6 7 Stage ml/ kg/ min VO2máx Curve VO2máx (Test at sea level) 12,2 17,4 26,1 34,8 43,5 52,2 64,4 0,0 10,0 20,0 30,0 40,0 50,0 60,0 70,0 1 2 3 4 5 6 7 Stage ml/ kg/ min VO2máx Capture de MVO2máx altitude x sea level 44,0 48,5 0,0 10,0 20,0 30,0 40,0 50,0 60,0 1 2 3 4 5 6 7 Stage ml O2 100g VE/ min MVO2máx altitude MVO2máx sea level Volume 78 - Special Edition - ARTICLE I - 2008 FIEP BULLETIN Janeiro and compares it to the level of the sea. The sample for the test was, due to the following criteria: Young athlete with 27 years of age, healthy, participating evidence of extreme exhaustion and high duration, experienced maximum tests more than once, not reported any commitment to health in recent months. The athlete was evaluated by the maximum oxygen consumption using the protocol test Astrand maximum cycle, which is applied to 838m above sea level, where the athlete is and realize their training and compared to the same test conducted at sea level. The results of that test were the athlete remained the same maximum oxygen uptake relative to 64.4 ml / kg / min in testing, and that their maximum oxygen consumption by the myocardium (MVO max.) 2 Suffered indirectly observed variations on will altitude at which it was tested. Analyzing the curve of the maximum oxygen consumption by the myocardium (MVO max.), I noticed that there was a greater uptake at sea level of 48.5 ml O 100g VE/min. 2 2 Compared to the same test will altitude of 838m, which was obtained O 100g VE 44 ml/min. the difference of 4.6 ml O 100g VE/min, 2 2 increasing their consumption to 9.5% at sea level. The athlete received significant performance at sea level.